Layanan Pengetahuan tentang COVID-19 di Lembaga Informasi - Rizki Nurislaminingsih (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Corona virus is causing anxiety for the community. Continuous reporting, rumors and the emergence of thousands of writings about corona on the internet add to the concern about the truth of the information content. Valid data and real information are needed to be a trusted source of knowledge. Information institutions becomes a bridge between the need for knowledge and the uncountable distribution of information. This paper aims to analyze the community's knowledge needs about COVID-19 and provide recommendations for activities that information agencies can undertake to meet needs. Patients with certain diseases, old age, and pregnant women need health knowledge according to the conditions of those who are considered to have a lower immune. Office workers, field workers, entrepreneurs, and students need knowledge of increased immunity, preventive measures and ways of treatment that are suitable for daily activities. Recommended activities that can be carried out by information institutions include: the data center can act as a valid data bank relating to the corona, the information center provides reliable information and the documentation center becomes document making agency. The library through the reference service provides reference knowledge about corona while the circulation service provides a collection of COVID-19.